Chronic kidney disease prevalence and associated risk factors in hypertensive adults at Burao general hospital, Burao City, Somaliland: a cross-sectional study - Yosef, Dek Kahin; Ali, Yusuf Ahmed (Frontiers in Cardiovascular Medicine, 2025)
BackgroundChronic kidney disease (CKD) is a significant global health challenge, particularly in low- and middle-income countries where hypertension is a prominent risk factor. This study aimed to assess the prevalence of CKD and its associated risk factors among hypertensive adults at the Burao General Hospital in Somaliland, Somalia.MethodsA cross-sectional study was conducted from January to July 2024, enrolling 262 hypertensive adults using consecutive sampling. Data were collected using structured questionnaires addressing sociodemographic factors, clinical characteristics, and lifestyle choices. Proteinuria levels and estimated glomerular filtration rates were assessed to confirm CKD diagnosis.ResultsThe prevalence of CKD among hypertensive patients was 52.67% (95% CI: 46.6%–58.7%). Significant associations were observed between CKD and factors such as age, proteinuria, diabetes, blood pressure control, and body mass index (BMI). Specifically, proteinuria was strongly linked to CKD (AOR: 10.72, 95% CI: 5.74–20.04). Individuals aged 34–41 years (AOR: 3.39, 95% CI: 0.99–11.54) and those classified as overweight (AOR: 3.37, 95% CI: 1.65–6.88) were at greater risk for CKD.ConclusionThe findings highlight a critical association between hypertension and CKD, emphasizing the need for targeted interventions to effectively manage hypertension and address modifiable risk factors. Understanding these relationships is vital for developing healthcare policies aimed at reducing CKD prevalence among adults in Burao City, Somaliland.